The effect of using modern technologies based on communication theory to develop the skills of reciting the Holy Quran among students of the curriculum system in the Kingdom of Saudi Arabia - Mamdouh, Ayman Aied Mohammed; Alfaifi, Essa Ahmad (Journal of Educational and Psychological Sciences, 2020)
This study aims at identifying the Effect of Using Technology and Modern Techniques (Ayat) that is based on the connectivism theory, in developing Quran recitation skills among curriculum's students of secondary school in Saudi Arabia. In order to achieve the study's objectives, the researcher uses the semi-experimental method. The study examines a sample of (71) students of secondary school curriculum system in the first semester of the academic year 1438H - 1439H in the government schools in Riyadh. They were divided into two equal groups (experimental and control). Students of the experimental group were taught according to the software program based on connectivism theory, and the others were taught in the traditional way. An oral test is used as a study tool to measure the existence of recitation skills (correct reading, smooth reading, recitation, and chanting), and to measure the Effect of Using Technology and Modern Technique in developing these skills. After analyzing the statistical data, the results of the study indicated the Effect of Using of the Modern Techniques, based on the connectivism theory, in the development of recitation skills (correct reading, smooth reading, recitation, and chanting) among curriculum's students of secondary school in Saudi Arabia. The study also showed a statistically significant difference of (0.05) between the average scores of the two groups in the post-measurement of the recitation test in the recitation skills such as (correct reading, smooth reading, recitation, and chanting) after adjusting the pre-measurement.
Keywords: Holy Quran Recitation Skills; Modern Techniques; Ayat; Connectivism Theory